How does increased vegetable varietal choice influence coffee farmers’ on-farm diversification strategies in the face of changing climate conditions? - Hethcote, Lindsey A. (2016)
Tesis (Mag.Sc.) -- CATIE, Escuela de Posgrado, Turrialba (Costa Rica), 2016